2018
DOI: 10.1093/mnras/sty1574
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Sagittarius and the Large Magellanic Cloud on the stellar disc of the Milky Way Galaxy

Abstract: We present N-body simulations of a Sagittarius-like dwarf spheroidal galaxy (Sgr) that follow its orbit about the Milky Way (MW) since its first crossing of the Galaxy's virial radius to the present day. As Sgr orbits around the MW, it excites vertical oscillations, corrugating and flaring the Galactic stellar disc. These responses can be understood by a two-phase picture in which the interaction is first dominated by torques from the wake excited by Sgr in the MW dark halo before transitioning to tides from S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
247
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(278 citation statements)
references
References 111 publications
(195 reference statements)
28
247
1
2
Order By: Relevance
“…Although there might be other mechanisms for creating density and velocity substructure in the disk (Debattista 2014;Faure et al 2014;Monari et al 2015Monari et al , 2016, the observed oscillations are roughly consistent with simulations of the disk's response to a large (> 10 9 M ) satellite or dark subhalo passing near, or through, the disk (Kazantzidis et al 2008, Younger et al 2008, Minchev et al 2009, Purcell et al 2011, Gómez et al 2013, Widrow et al 2014, Laporte et al 2016. Corrugations have also been observed in HI gas and young stellar populations in the Milky Way (Spicker & Feitzinger 1986;Levine et al 2006), and in external galaxies (Matthews & Uson 2008a,b).…”
Section: Disk Substructuresupporting
confidence: 76%
“…Although there might be other mechanisms for creating density and velocity substructure in the disk (Debattista 2014;Faure et al 2014;Monari et al 2015Monari et al , 2016, the observed oscillations are roughly consistent with simulations of the disk's response to a large (> 10 9 M ) satellite or dark subhalo passing near, or through, the disk (Kazantzidis et al 2008, Younger et al 2008, Minchev et al 2009, Purcell et al 2011, Gómez et al 2013, Widrow et al 2014, Laporte et al 2016. Corrugations have also been observed in HI gas and young stellar populations in the Milky Way (Spicker & Feitzinger 1986;Levine et al 2006), and in external galaxies (Matthews & Uson 2008a,b).…”
Section: Disk Substructuresupporting
confidence: 76%
“…Idealized simulations show that including density inhomogeneities in the gaseous disk heats up stellar disks (Struck & Elmegreen 2017), as does allowing for interactions with massive satellites (Laporte et al 2016). Such conditions were common at early cosmic times in the Latte simulation analyzed here.…”
Section: Radial Migrationmentioning
confidence: 79%
“…It will also be mandatory to move away from the epicyclic approximation (McGill & Binney 1990;Sanders & Binney 2015). Once this will be done, in the absence of strong resonance overlaps, a complete dynamical model of the presentday Milky Way disc could then in principle finally be built by applying, on top of the trapped distribution function near the main resonances of each perturber, our previous Eulerian treatment of perturbations (Monari et al 2016a) for the other perturbers, even including vertical perturbations and "bending" modes of the disc (Widrow et al 2014;Xu et al 2015;Laporte et al 2016). …”
Section: Resultsmentioning
confidence: 99%